Somalia : Technical Assistance Report-Internal Audit and Accounting Training for the Central Bank of Somalia. (IMF Staff Country Reports; Country Report, 2019)
The CBS has taken steps to establish important pillars of a proper policy framework for financial reporting, auditing, and internal controls by approving the Internal Audit and Audit Committee Charters and is committed to address the remaining shortcomings in these areas. The Internal Audit Department (IAD) has made progress by initiating risk assessments of the various CBS business units and recruiting an Information Technology (IT) professional to join the team. The Accounting and Finance Department (AFD) is making progress in implementing accrual accounting, and accounting for foreign exchange operations (International Accounting Standard (IAS) 21), and has created a new role of Reconciliation Officer to ensure all cash transactions are recorded properly. However, the IAD functions without a director, which places the internal audit staff at a severe disadvantage to other departments and limits their authority to effectively implement their program. Also, while the mission team has stressed the importance of adopting International Financial Reporting Standards (IFRS) during this mission and the previous mission, the CBS has not formally indicated that it will adopt this framework.2 High priority recommendations were made to address these shortcomings. See Table 1 for homework assignments and high priority tasks.3.